Aplicabilidad del principio de celeridad en el procedimiento civil colombiano y la pérdida automática de la competencia de los jueces (2019)
Justice administration in Colombia and the way it should be served in the judicial processes that tend to search for justice, may it be implied or demanded. This time, the application of the principles guarantees the process in itself and throught its development. It is therefore, that the haste principle takes a fundamental role within the legal system as an ensuring mechanism against procedure. However, the bottleneck and judicial lateness is one of the most common problems in the judicial system, the haste principle is not watched by the technical operators and the whole set of employees of the Judicial Branch, this results violating rights and liberties which has as a consequence the automatic los of judge’s competence. Therefore, the following investigation aims to explain the applicability of the haste principle as a procedural guarantee within the Colombian civil procedure and the automatic loss of the judge’s competence due to its innaplicability.